Development of API Middleware and Mobile Application for a Job marketplace by Using RESTful API and Mobile Development Framework - Wahyudi, Evan Tirta; Erwin, Alva; Lim, Charles (Swiss German University, 2020)
The research is conducted based on the nationwide goals of Indonesia proposed in the Nawacita document, where one of the big goals is to improve the human resource greatly. Providing a good medium such as a job marketplace can be part of improving the human resource. Since most of Indonesian citizen nowadays has easy access to internet, which can ease their way of using a job marketplace application. Creating a job marketplace application may minimize a number of unemployment in Indonesia. Addition to that, through a focus group discussion, it has been discovered that respondents find job marketplace such as JobStreet and Indeed jobs does not satisfy respondents’ UI and UX view towards the application. The objective of this research is to create a job marketplace mobile application that is useful and easy to use for users. The prototype mobile application is developed using react native, and a middleware that is developed using Express JS is made alongside to bridge data to the mobile application. To assess the prototype mobile application, two evaluation method is used which is User Experience Questionnaire (UEQ) and Questionnaire User Interface Satisfaction (QUIS). 6 respondents were allowed to examine prototype application, and answer the questionnaire. The result of the evaluation both shows positive results from both questionnaires.